Are venture capitalists firefighters? A study of the influence and impact of venture capital firms - Fredriksen, Oystein; Olufsson, Christer; Wahlbin, Clas.
This paper explores the question of the influence and impact of venture capitalists on the development of portfolio companies. Influence on the portfolio companies in various aspects-as perceived both by venture capitalists and by managers of portfolio companies-is analysed against both parties' perceptions of economic development and other aspects of the development so far, and their subjective outcome. It is found that influence tends to be perceived as either low or high, and that high influence is associated with better development in some non-economic aspects but not in economic development. The two parties have the same view of development, but the subjective outcome has been perceived as higher by the managers of portfolio companies than by the venture capitalists when influence is high. The results are consistent with a hypothesis that venture capitalists are 'firefighters' that allocate their scarce time to portfolio companies with problems.
It is found that Swedish venture capitalists concentrate their scarce time resources on carrying out 'firefighting' activities to save portfolio companies who are in trouble. This usually has an immediate impact on economic development.
Keywords: Venture capitalists; Venture capital firms